Genetic and methylation profiles distinguish benign, malignant and spitzoid melanocytic tumors. Issue 9 (11th July 2022) - Zaremba, Anne; Jansen, Philipp; Murali, Rajmohan; Mayakonda, Anand; Riedel, Anna; Philip, Manuel; Rose, Christian; Schaller, Jörg; Müller, Hansgeorg; Kutzner, Heinz; Möller, Inga; Stadtler, Nadine; et al.
Abstract: Accurate classification of melanocytic tumors is important for prognostic evaluation, treatment and follow‐up protocols of patients. The majority of melanocytic proliferations can be classified solely based on clinical and pathological criteria, however in select cases a definitive diagnostic assessment remains challenging and additional diagnostic biomarkers would be advantageous. We analyzed melanomas, nevi, Spitz nevi and atypical spitzoid tumors using parallel sequencing (exons of 611 genes and 507 gene translocation analysis) and methylation arrays (850k Illumina EPIC). By combining detailed genetic and epigenetic analysis with reference‐based and reference‐free DNA methylome deconvolution we compared Spitz nevi to nevi and melanoma and assessed the potential for these methods in classifying challenging spitzoid tumors. Results were correlated with clinical and histologic features. Spitz nevi were found to cluster independently of nevi and melanoma and demonstrated a different mutation profile. Multiple copy number alterations and TERT promoter mutations were identified only in melanomas. Genome‐wide methylation in Spitz nevi was comparable to benign nevi while the Leukocytes UnMethylation for Purity (LUMP) algorithm in Spitz nevi was comparable to melanoma. Histologically difficult to classify Spitz tumor cases were assessed which, based on methylation arrays, clustered between Spitz nevi and melanoma and in terms of genetic profile or copy number variations demonstrated worrisome features suggesting a malignant neoplasm. Comprehensive sequencing and methylation analysis verify Spitz nevi as an independent melanocytic entity distinct from both nevi and melanoma. Combined genetic and methylation assays can offer additional insights in diagnosing difficult to classify Spitzoid tumors. Abstract : What's new? Most melanocytic lesions can be accurately classified and diagnosed by clinical and pathological examination, but some lesions are very challenging to assess. Here, the authors used DNA sequencing and methylation analysis to characterise various types of melanocytic lesions, including nevi, melanomas, Spitz nevi and atypical spitzoid tumors. They found that Spitz nevi had a distinctive genetic and epigenetic profile compared to melanomas and nevi. These techniques also showed promise for diagnosing atypical spitzoid tumors, which are difficult to classify histologically.